Banking panic risk and macroeconomic uncertainty - Jakob Guldbæk Mikkelsen; Johannes Poeschl (Danmarks Nationalbank, 2020)
We show that systemic risk in the banking sector breeds macroeconomic uncertainty. We develop a model of a production economy with a banking sector where financial constraints of banks can lead to disastrous banking panics. We find that a higher probability of a banking panic increases uncertainty in the aggregate economy. We explore the implications of this banking panic-driven uncertainty for business cycles, asset prices and macroprudential regulation. Banking panic-driven uncertainty amplifies business cycle volatility and increases risk premia on asset prices. A countercyclical capital buffer lowers both the probability of banking panics and aggregate uncertainty.
Keywords: E44; G12; G21; G28; 330; Banking Panics; Systemic Risk; Endogenous Uncertainty; Macroprudential Policy